Infliximab Selectively Modulates the Circulating Blood Monocyte Repertoire in Crohn's Disease. Issue 12 (December 2016) - Slevin, Stephanie M.; Dennedy, Michael Conall; Connaughton, Eanna P.; Ribeiro, Andreia; Ceredig, Rhodri; Griffin, Matthew D.; Egan, Laurence J.
Abstract : Background: Infliximab (IFX), an anti-tumour necrosis factor alpha (TNFα) monoclonal antibody, provides clinical benefits in treating Crohn's disease (CD) but its mechanisms of action are not fully elucidated. This study investigated blood monocyte repertoires and the acute effects of IFX infusion on monocyte subset phenotype and function in IFX-treated patients with CD. Methods: Monocytes and monocyte subsets were enumerated and phenotypically characterized by multicolor flow cytometry in freshly isolated blood from healthy controls (n = 21) and patients with CD treated with (IFX, n = 24) and without (non-IFX, n = 20) IFX. For the IFX-CD group, blood was sampled immediately before (tough-IFX) and after (peak-IFX) infusion. Monocyte responses to lipopolysaccharide were analyzed by whole-blood intracellular cytokine staining. Results: Non-IFX and IFX-CD patients had increased numbers of intermediate (CD14 ++ CD16 + ) monocytes compared with healthy controls, whereas classical (CD14 ++ CD16 + ) and nonclassical (CD14 dim CD16 ++ ) monocytes were numerically reduced in the IFX-CD group alone. In all groups, monocyte subsets expressed high surface levels of transmembrane (tm)TNFα. After IFX infusion, a significant reduction in monocyte numbers occurred. Post-IFX monocytopenia was proportionately greatest for classical and intermediate subsets, correlated with postinfusion IFX levels and was not associated with monocyte apoptosis. In contrast, lipopolysaccharide-induced production of TNFα and IL-12 by monocytes was significantly reduced in peak-IFX compared with trough-IFX blood samples. Conclusions: Actively managed CD is associated with monocyte repertoire skewing suggestive of chronic inflammatory stimulation. Infused IFX acutely targets monocytes, likely by binding to tmTNFα, resulting in a non–apoptosis-related decline in circulating monocyte numbers and blunting of the inflammatory response of monocytes remaining in the blood. Abstract : Article first published online 4 November 2016.